Seasonal variations of physico-chemical properties of the Great Vedaranyam Swamp, Point Calimere Wildlife Sanctuary, South-east coast of India - Ramalingam Manikannan; Subramanian Asokan; Abdul Hameed Mohamed Samsoor Ali (African Journal of Environmental Economics and Management, 2019)
The present study was attempted on the physico-chemical variability of the Great Vedaranyam Swamp of the Point Calimere Wildlife Sanctuary, South-east coast of India. Seasonal variation study was carried out to examine level of varying physico-chemical parameters such as temperature, salinity, pH, dissolved oxygen, nitrate, nitrite, electrical conductivity, phosphate, turbidity, total dissolved solids and water depth. The physico-chemical parameters have exhibited considerable seasonal and spatial variations. The qualitative study revealed the present status of the physico-chemical parameters, which would be very helpful for policy makers to take precautionary measures to save the swamp.